Evaluation of the thermal stability and the protective efficacy of spray-dried HPV vaccine, Gardasil® 9. Issue 7 (3rd August 2019) - Kunda, Nitesh K.; Peabody, Julianne; Zhai, Lukai; Price, Dominique N.; Chackerian, Bryce; Tumban, Ebenezer; Muttil, Pavan
ABSTRACT: High-risk human papillomavirus (HPV) types are responsible for nearly all cases of cervical cancers. Cervarix® and Gardasil® 9 are the current prophylactic vaccines available that protect against the majority of HPVs associated with cancer. Although these vaccines are highly effective, HPV vaccine implementation has been slow, particularly in low-and-middle income countries. Major barriers to the widespread availability of the HPV vaccines is its cost and the requirement for continuous refrigeration (2–8°C). Here, we used spray drying along with stabilizing excipients to formulate a thermostable Gardasil® 9 vaccine. We evaluated the immunogenicity and protective efficacy of the vaccine in mice immediately after spray drying and following storage for three months at 4°C, 25°C, and 40°C. The immunogenicity studies were performed using Gardasil® 9 as a whole antigen, and not individual HPV types, for ELISA. At the dose tested, the spray dried vaccine conferred protection against HPV following storage at temperatures up to 40°C. In addition to the spray-dried vaccine, our studies revealed that the Gardasil® 9 vaccine, as currently marketed, may be stored and transported at elevated temperatures for up to 3 months without losing efficacy, especially against HPV16. This study is critical, as a thermostable vaccine will decrease vaccine cost associated with cold-chain maintenance and could increase vaccine access and coverage, especially in remote regions of the world.